7T ultra‐high field body MR imaging with an 8‐channel transmit/32‐channel receive radiofrequency coil array. Issue 7 (9th May 2018) - Rietsch, Stefan H. G.; Orzada, Stephan; Maderwald, Stefan; Brunheim, Sascha; Philips, Bart W. J.; Scheenen, Tom W. J.; Ladd, Mark E.; Quick, Harald H.
Abstract : Purpose: In this work, a combined body coil array with eight transmit/receive (Tx/Rx) meander elements and with 24 receive‐only (Rx) loops (8Tx/32Rx) was developed and evaluated in comparison with an 8‐channel transmit/receive body array (8Tx/Rx) based on meander elements serving as the reference standard. Methods: Systematic evaluation of the RF array was performed on a body‐sized phantom. Body imaging at 7T was performed in six volunteers in the body regions pelvis, abdomen, and heart. Coil characteristics such as signal‐to‐noise ratio, acceleration capability, g‐factors, S‐parameters, noise correlation, and B1+ maps were assessed. Safety was ensured by numerical simulations using a coil model validated by dosimetric field measurements. Results: Meander elements and loops are intrinsically well decoupled with a maximum coupling value of −20.5 dB. Safe use of the 8Tx/32Rx array could be demonstrated. High gain in signal‐to‐noise ratio (33% in the subject's center) could be shown for the 8Tx/32Rx array compared to the 8Tx/Rx array. Improvement in acceleration capability in all investigations could be demonstrated. For example, the 8Tx/32Rx array provides lower g‐factors in the right–left and anterior–posterior directions with R = 3 undersampling as compared to the 8Tx/Rx array using R = 2. Both arrays are very similar regarding their RF transmit performance. Excellent image quality in the investigated body regions could be achieved with the 8Tx/32Rx array. Conclusion: In this work, we show that a combination of eight meander elements and 24 loop receive elements is possible without impeding transmit performance. Improved SNR and g‐factor performance compared to an RF array without these loops is demonstrated. Body MRI at 7T with the 8Tx/32Rx array could be accomplished in the heart, abdomen, and pelvis with excellent image quality.